Improving student achievement first class v elementary school no. 21 kapuh in first subjects ips on natural appearance using interactive learning model semester academic year 2016/2017 - Puat Syafruddin (Jurnal Ilmiah Pendidikan Scholastic, 2017)
The purpose of this study is to prove that the use of the environment around the school to enhance students' understanding of the events of Islamic religious education in students of Class I V In S D Affairs No. 21 Kapuh. This study uses a class action approach. The study population was taken of all students in grade IV , the data collection techniques used artificial teacher learning achievement test. Actions performed a total of two cycles. Data analysis techniques used analysis of the percentage of change in the results of the evaluation study before and after tutoring services with peer tutors. Thus there is an increasing mastery learning students from the first cycle to the second cycle. Based on the above, it can be made a conclusion as follows: " Improving Student Achievement First Class V Elementary School No. 21 Kapuh In first Subjects PS On Natural Appearance Using Interactive Learning Model Semester Academic Year 2016/2017 "